Evidence-based topical management of chronic wounds according to the T.I.M.E. principle Evidenzbasierte topische Therapie chronischer Wunden nach dem T.I.M.E.-Prinzip - Klein, Silvan; Schreml, Stephan; Dolderer, Juergen; Gehmert, Sebastian; Niederbichler, Andreas; Landthaler, Michael; Prantl, Lukas (Journal der Deutschen Dermatologischen Gesellschaft, 2013)
The number of patients suffering from chronic wound healing disorders in Germany alone is estimated to be 2.5-4 million. Therapy related expenses reach 5-8 billion Euros annually. This number is partially caused by costly dressing changes due to non-standardized approaches and the application of non-evidence-based topical wound therapies. The purpose of this paper is to elucidate a straightforward principle for the management of chronic wounds, and to review the available evidence for the particular therapy options. The T.I.M.E.-principle (Tissue management, Inflammation and infection control, Moisture balance, Epithelial [edge] advancement) was chosen as a systematic strategy for wound bed preparation. Literature was retrieved from the PubMed and Cochrane Library databases and subjected to selective analysis. Topical wound management should be carried out according to a standardized principle and should further be synchronized to the phases of wound healing. Despite the broad implementation of these products in clinical practice, often no benefit exists in the rate of healing, when evaluated in meta-analyses or systematic reviews. This insufficient evidence is additionally limited by varying study designs. In case of non-superiority, the results suggest to prefer relatively inexpensive wound dressings over expensive alternatives. Arbitrary endpoints to prove the effectiveness of wound dressings, contribute to the random use of such therapies. Defining rational endpoints for future studies as well as the deployment of structured therapy strategies will be essential for the economical and evidence-based management of chronic wounds. © The Authors | Journal compilation © Blackwell Verlag GmbH, Berlin.
CRIS-Team Scopus Importer:2024-12-11